Physicochemical properties of turmeric (Curcuma longa L.) and black pepper (Piper nigrum) enriched ice cream - Mirela Lučan Čolić; Martina Antunović; Jasmina Lukinac; Jurislav Babić; Antun Jozinović; Bojan Matijević; Tihana Nikolić; Marko Jukić (Mljekarstvo)
The effect of turmeric powder and a mix of turmeric powder and black pepper on the physicochemical properties of ice cream samples was examined. Enriched ice creams were manufactured by adding turmeric powder at levels of 0.5 %, 1.0 % and 2.0 %, with or without 0.02 % black pepper and compared with the control ice cream sample. Samples were analysed for proximate composition, pH value, water activity (aw), rheological properties, overrun, fat destabilization, hardness, melting properties, and colour parameters. The results of the study showed that the addition of spices significantly increased pH values (from 6.66 to 6.73), total solids (from 36.43 to 37.53 %), and carbohydrate contents (from 21.47 to 22.53 %) of the samples. Furthermore, this enrichment leads to an increase in the viscosity (from 0.44 to 0.70 Pa s) and thixotropic behaviours of ice cream mixes. Enriched ice creams had higher air incorporation, lower fat destabilization degree, and softer texture. In terms of melting properties, the melting resistance of ice cream samples was enhanced with the addition of spices. The colour properties of ice creams were significantly (p<0.05) affected by turmeric addition, while there was no difference between samples with and without black pepper. To conclude, turmeric powder and black pepper can be used for the development of functional turmeric-black pepper ice cream with acceptable physicochemical properties.